International migration and the global economic order : an overview - Solimano, Andrés 1956- (Policy research working paper, 2001)
Global capitalism, vintage 21st century, is less friendly to the international migration of unskilled people than were previous waves of globalization (such as that of the late 19th century). A freer regime for international migration could help to reduce global economic inequality, improve the allocation of world resources and ease labor shortages during periods of rapid growth. But the flight of human capital talent, and entrepreneurs can be detrimental for developing countries